THE EFFECT OF DIGITAL PROMOTION ON INCREASED SALES (Case Study At The Emyu Bookstore in Bangkinang City) - L. Yansen; Librina Tria Putri; Muhammad Salis (Jurnal Riset Manajemen Indonesia, 2021)
This research aims to determine the effect of digital promotion on increased sales at the Emyu Bookstrore in Bangkinang City. This research was conducted at Emyu Bookstore in Bangkinang City for 2 months, from July to August 2020. The types of data used are quantitative data and qualitative data, while the data sources in this study are primary data and secondary data. Data collection techniques used in this study were questionnaires, file research, observation and interviews. The population in this study were all consumers at the Emyu Bookstore in Bangkinang City in 2019, amounting to 2.844 consumers and based on the Slovin formula with 10% inaccuracy level, the number of samples in this study is 100 consumers. Data analysis carried out by simple linear regression model and hypothesis testing carried out by the t test at the rate of 5%. Based on the result of the research it can be concluded that digital promostion has a significant effect on increased sales at the Emyu Bookstrore in Bangkinang City. The closeness of the relationship between digital promotion varable on increased sales at the Emyu Bookstoore in Bangkinang City is very strong because the correlation coefficient (r) value is obtained 92,2%.